2007
DOI: 10.1086/510812
|View full text |Cite
|
Sign up to set email alerts
|

Attributable Cost and Length of Stay for Patients With Central Venous Catheter—Associated Bloodstream Infection in Mexico City Intensive Care Units A Prospective, Matched Analysis

Abstract: In this study, the duration of ICU stay for patients with central venous catheter-associated BSI was significantly longer than that for control patients, resulting in increased healthcare costs and a higher attributable mortality. These conclusions support the need to implement preventive measures for hospitalized patients with central venous catheters in Mexico.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
2
8

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 38 publications
(20 reference statements)
3
62
2
8
Order By: Relevance
“…), de ahí que se recomiende la utilización de ambos indicadores. Un ejemplo de complementariedad podría ser la monitorización de los consumos en todo el centro y reservar la medición del grado de cumplimiento de las recomendaciones para diseñar o evaluar intervenciones específicas en determinadas unidades (cuidados críti-cos, servicios quirúrgicos) o para diseñar y evaluar intervenciones sobre determinados procedimientos, donde un ejemplo paradigmático puede ser la información publicada sobre la prevención de bacteriemias asociadas a dispositivos intravasculares [23][24] . Los indicadores de resultados elegidos se basan en medidas de prevalencia por dos motivos, porque permiten un visión global de la situación en el centro, dado que la población diana del programa de actualización son los aproximadamente 3.000 trabajadores del centro, y porque los estudios de prevalencia anuales son uno de los pilares básicos del sistema de vigilancia epidemiológica del centro desde el año 1991.…”
Section: Discussionunclassified
“…), de ahí que se recomiende la utilización de ambos indicadores. Un ejemplo de complementariedad podría ser la monitorización de los consumos en todo el centro y reservar la medición del grado de cumplimiento de las recomendaciones para diseñar o evaluar intervenciones específicas en determinadas unidades (cuidados críti-cos, servicios quirúrgicos) o para diseñar y evaluar intervenciones sobre determinados procedimientos, donde un ejemplo paradigmático puede ser la información publicada sobre la prevención de bacteriemias asociadas a dispositivos intravasculares [23][24] . Los indicadores de resultados elegidos se basan en medidas de prevalencia por dos motivos, porque permiten un visión global de la situación en el centro, dado que la población diana del programa de actualización son los aproximadamente 3.000 trabajadores del centro, y porque los estudios de prevalencia anuales son uno de los pilares básicos del sistema de vigilancia epidemiológica del centro desde el año 1991.…”
Section: Discussionunclassified
“…Central line-associated bloodstream infections (CA-BSIs) are associated with significant morbidity, mortality, and costs [1][2][3]. A special high risk patient group for CA-BSIs are the hematological oncology patients, because nearly 100% of these patients require indwelling central venous catheters for therapy and keep them during neutropenic episodes.…”
Section: Introductionmentioning
confidence: 99%
“…In various studies, increases in length of stay, cost, and attributable mortality have all been reported as consequences of CLABSI [1,[24][25][26][27]. In Argentina, Rosenthal et al found that CLABSI resulted in an extra 12 days of hospitalization and 4,888 US dollars in costs [1].…”
Section: Discussionmentioning
confidence: 99%